Analysis of the application of behavioral accounting aspects in the management of village fund allocation in Pineleng Satu Village of Pineleng District in Minahasa Regency - Meruntu, Lenfiane Kristefa; Sondakh, Jullie J.; Manossoh, Hendrik (The Contrarian : Finance, Accounting, and Business Research, 2024)
This study aims to analyze: (1) the application of behavioral accounting aspects in the management of village fund allocations in Pineleng Satu Village of Pineleng District in Minahasa Regency, and (2) factors that cause delays in completing the accountability report. This type of research is qualitative with a case study approach. Determination of research subjects using purposive sampling technique. This research uses data collection techniques through interviews and documentation. The data analysis techniques are data reduction, data presentation, conclusion drawing, and data verification. Data validity tests include credibility tests with triangulation of sources and techniques, and dependability tests. The results showed: (1) the application of behavioral accounting aspects in the management of village fund allocations in Pineleng Satu Village has not been fully implemented properly. This can be seen from the aspect of reporting requirements where the village government is slow in completing the accountability report, resulting in the accountability report not being reported according to the specified time. (2) The first factor that causes delays in completing the accountability report is related to human resources and the second factor is the behavior of implementers in collecting complementary documents for the accountability report.